RESEARCH Research of Factors Affecting the Implementation of Vietnam Public Accounting Standards at Revenue – Generating Administrative and Non – Business Units - Nhinh Nguyen Thi; Trinh Thanh, Binh; Thi Ngoc, Ha Nguyen; Truc Quynh, An Vu (International Journal of Scientific Research and Management (IJSRM), 2023)
By the method of summarizing documents, the article aims to identify the factors affecting the application of international public accounting standards in some countries, along with the views of the authors on the factors that will affect when applying Public Accounting Standards (PAS) in units within the scope of application of Accounting Standards. public mathematics in Vietnam. Vietnam is in the process of completing the development of public accounting standards through stages, in order to help the information provided on financial statements be more transparent and comparable. The factors identified through the awareness of accountants at the revenue generating public service delivery unit include: Level of training and professionalism, implementation costs, support of consulting organizations and managers and information technology application. On that basis, the article is a premise to implement an empirical research model on the influence of factors when applying public accounting standards at revenue – generating administrative and non – business units in Vietnam.